AUTOMATED SYSTEM OF RESULTS TREATMENT OF ULTRASONIC MEASUREMENTS OF ELASTIC WAVES VELOCITIES IN ROCK-RESERVOIRS BY INVARIANT-POLARIZE METHOD - Prodayvoda, G.; Vyzhva, S.; Onanko, Yu.; Onanko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The automated system is created for numerical analysis and visualization of ultrasonic measurings of velocities anisotropy parameters of elastic quasiprimary, "rapid" and "slow" quasisecondary waves in rock-reservoirs by invariant-polarize method. The sandstones elastic constants of Volino – Podil’skiy region are got, the elastic symmetry of which is rhombic.